Nilai-Nilai Religius Dalam Novel Buya Hamka Karya Ahmad Fuadi - Alfiyah Alfiyah; Linggua Sanjaya Usop; Misnawati Misnawati; Alifiah Nurachmana; Paul Diman (Universitas Palangka Raya, 2023)
The aim of this research is to (1) describe the religious values in the form of belief values in the novel